Fossil Neuroptera of the Lower Cretaceous of Baisa, East Siberia. Part 4: Psychopsidae. - Makarkin, Nikolai Vladimir (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Baisopsychops lambkini gen. et sp. n. from the Lower Cretaceous of Baisa in East Siberia is described. Nomenclatural Actslambkini Makarkin, 1997 (Baisopsychops), spec. n.Baisopsychops Makarkin, 1997 (Psychopsidae), gen. n.